Mapping User’s Activities and Space Preferences in the Academic Business Library - Simpson, Heather; Given, Lisa (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Examines patrons’ use of spaces in a small academic library using observation and GIS technology. A questionnaire was used to assess patrons’ perceptions of space use. Results of the study can guide the design of library spaces and help researchers and librarians better understand patrons’ needs in these settings. Cette communication examine l’utilisation de l’espace-usager d’une petite bibliothèque universitaire par l’observation et la technologie SIRS. Un questionnaire a été utilisé pour évaluer la perception des usagers de l’aménagement des lieux. Les résultats de cette étude peuvent guider la conception de l’aménagement des bibliothèques et aider les chercheurs et les bibliothécaires à mieux comprendre les besoins des usagers dans ces lieux.